The Farmer's Almanack, Calculated on a New and Improved Plan, For the Year of Our Lord, 1816. Being Bissextile or Leap-Year, and Fortieth of the Independence of America. - Thomas, Robert Bailey, 1766-1846. (Tufts University. Tisch Library., 2018)
24 leaves.